'Out through the door and in through the window?': Positioning colonial nostalgia for French India in Puducherry. (1st September 2022) - Jørgensen, Helle
The former French India has held a distinctive place in metropolitan French discourses and sentiments of colonial nostalgia which have been subject to sustained analysis. French India is thus part of a larger body of research exploring colonial nostalgia both as a general phenomenon and in a specific regional context. However, the corresponding imaginaries in what after its decolonization became the Indian Union Territory of Puducherry have remained marginalized in research. Yet regardless of the frequently naturalized expectation that the colonial metropoles should be its natural habitat, colonial nostalgia is not something that only occurs among the former colonial powers, and colonial nostalgia is in fact expressed in many ways in present-day Puducherry. This ethnographic study shows that if we are to understand the production and roles of colonial nostalgia we need to analyse it not merely from the perspective of the former colonial powers, but also as it occurs in the former colonies. Indeed, we should question how separate such discourses, imaginaries and sentiments of colonial nostalgia are, and redirect our attention to interrogating how they interact and may be coproduced in a broader, often ambiguous post/colonial field where postcolonial interests in the former colony are equally at stake.